2020
DOI: 10.1111/cts.12748
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics in Practice: Estimating the Clinical Actionability of Pharmacogenetic Testing in Perioperative and Ambulatory Settings

Abstract: Most literature describing pharmacogenetic implementations are within academic medical centers and use single‐gene tests. Our objective was to describe the results and lessons learned from a multisite pharmacogenetic pilot that utilized panel‐based testing in academic and nonacademic settings. This was a retrospective analysis of 667 patients from a pilot in 4 perioperative and 5 outpatient cardiology clinics. Recommendations related to 12 genes and 65 drugs were classified as actionable or not actionable. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…20 In a study comprising 600 adult patients seen in outpatient or perioperative cardiology clinics and another studying 122 patients with cardiac catheterization, 16.1% and 20% of patients, respectively, were identified to have a PGx variant that may affect the metabolism of a currently taken medication. [21][22] When exposure inquiry was expanded to medication use in the past 20 years, 80% of English adults had exposure to at least 1 drug with PGx guidance. 23 This compares to the 15% (68/452) of pediatric patients in our study who had a matching prescription within 2 years before or after PGx testing.…”
Section: Results In Context With Previous Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…20 In a study comprising 600 adult patients seen in outpatient or perioperative cardiology clinics and another studying 122 patients with cardiac catheterization, 16.1% and 20% of patients, respectively, were identified to have a PGx variant that may affect the metabolism of a currently taken medication. [21][22] When exposure inquiry was expanded to medication use in the past 20 years, 80% of English adults had exposure to at least 1 drug with PGx guidance. 23 This compares to the 15% (68/452) of pediatric patients in our study who had a matching prescription within 2 years before or after PGx testing.…”
Section: Results In Context With Previous Literaturementioning
confidence: 99%
“…In a study of Chinese children, up to 9% of patients received at least one medication associated with a CPIC guideline 20 . In a study comprising 600 adult patients seen in outpatient or perioperative cardiology clinics and another studying 122 patients with cardiac catheterization, 16.1% and 20% of patients, respectively, were identified to have a PGx variant that may affect the metabolism of a currently taken medication 21–22 . When exposure inquiry was expanded to medication use in the past 20 years, 80% of English adults had exposure to at least 1 drug with PGx guidance 23 .…”
Section: Discussionmentioning
confidence: 99%
“…6 We hypothesize that patients hospitalized with COVID-19 require medications that are affected by PGx for treatment of acute symptoms and chronic conditions. Although prior investigations have characterized the use of PGx-guided medications in primary care 7 , perioperative, and cardiovascular disease cohorts [8][9][10] we are not aware of prior assessments of the potential value of PGx testing among individuals with COVID-19.…”
Section: More Than 200 Medications Have Pharmacogenomic Information Imentioning
confidence: 99%
“…12 Mission Health developed an outpatient clinic for PGx consultations. 39 40 While the community pharmacy setting has long been a proposed site for integration of PGx into modern healthcare practices, similar barriers persist. 41,42 However, recent studies have demonstrated the viability of PGx work in general in community pharmacies.…”
Section: Introduction and Background Of Pharmacogenomics Across Health-care Settingsmentioning
confidence: 99%
“… 1 Further growth is expected within ambulatory care with pilots such as MedStar Health’s ambulatory-based pilot estimating PGx clinical actionability. 40 …”
Section: Introduction and Background Of Pharmacogenomics Across Health-care Settingsmentioning
confidence: 99%